DOI: 10.31274/etd-180810-4184
|View full text |Cite
|
Sign up to set email alerts
|

Development of rural curve driving models using lateral placement and prediction of lane departures using the SHRP 2 naturalistic driving data

Abstract: CHAPTER 1: INTRODUCTION Background Background on SHRP 2 Naturalistic Driving Study Background on SHRP 2 Roadway Information Database Previous Research Factors contributing to run off the road crashes Crash Surrogates Related to Roadway Departures Vehicle Path Trajectories and Lateral Position within curves

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Oneyear et al compared driver braking behavior at different rural stopped controlled intersections with different traffic control devices (TCDs) using the SHRP2 NDS data (14). They developed a linear mixed effects regression model and observed that overhead flashing beacons and on-pavement signing increase the distance at which drivers begin braking.…”
Section: Studies At Intersections Using Shrp2 Nds Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Oneyear et al compared driver braking behavior at different rural stopped controlled intersections with different traffic control devices (TCDs) using the SHRP2 NDS data (14). They developed a linear mixed effects regression model and observed that overhead flashing beacons and on-pavement signing increase the distance at which drivers begin braking.…”
Section: Studies At Intersections Using Shrp2 Nds Datamentioning
confidence: 99%
“…They developed a linear mixed effects regression model and observed that overhead flashing beacons and on-pavement signing increase the distance at which drivers begin braking. They attempted to build a model of gap acceptance but were ultimately unsuccessful because of the small data size and video quality (14). Kim et al compared different driver distractions in carfollowing models based on driver eye-glancing behavior from a 100-car NDS database using decision tree analysis (15).…”
Section: Studies At Intersections Using Shrp2 Nds Datamentioning
confidence: 99%